Adopting Green Marketing on Consumers’ Purchase Intention in Retail Market of Coating Industry in Thailand - Rachanakul, Sarawut; Wiriyakitjar, Rawida (Journal of Posthumanism, 2025)
As environmental concerns increasingly shape consumer preferences. This study examines how green marketing, green perceived value, and green brand trust influence green purchase intention and brand love in the emerging green retail market of Southeast Asia, with a case study in Thailand. The study also explores the mediating role of green brand trust and the moderating effect of green knowledge. Data were collected from 510 consumers via a questionnaire and analyzed using Partial Least Squares Structural Equation Modeling. Results show that green marketing and green perceived value significantly enhance green brand trust, which positively impacts both green purchase intention and brand love. Green brand trust mediates the effects of green marketing and perceived value on these outcomes. However, green knowledge did not significantly moderate these relationships. The findings highlight the importance of transparent green marketing in fostering consumer trust, loyalty, and emotional engagement.